Material Property-Manufacturing Process Optimization for Form 2 Vat-Photo Polymerization 3D Printers - Garcia, Elisa Aznarte; Ayranci, Cagri; Qureshi, Ahmed Jawad (Journal of Manufacturing and Materials Processing, 2020)
This study aims to assess the effect of printing parameters on the final tensile properties of 3D printed specimens printed through a popular vat-photopolymerization printer—‘Form 2’. Elastic modulus, ultimate tensile strength and strain at break are analyzed as a function of process parameters in order to provide an optimized print parameter configuration. Design of Experiments (DoE) using Taguchi’s techniques was used to print the test samples. Tensile tests were performed on the 3D printed specimens following the ISO-527 standard. The post-experiment analysis provide more insight on the effect of each studied factor on the elastic properties of these specimens. To complete this study, an analysis of the total manufacturing process time is presented with respect to the aforementioned elastic properties. The study shows that the parts are orthotropic and sensitive to layer height and post-curing. The orthotropic behaviour can be substantially reduced by appropriate post-curing process, resulting in high improvement of the elastic modulus and ultimate tensile strength. This paper is of special interest to researchers and users of desktop 3D printers who wish to improve the performance of their equipment, compare printing capabilities or assess the effect of different hardware on a single resin.